Kamus besar Arab-Melayu dewan = قاموس بسر عرب - ملايو ديوان - Khalid, Osman; Awang Mat dahan, Hasan Basri; Al-muhammadi, Abdul Halim; Chik, Abdul Rahman (Dewan Bahasa dan Pustaka, 2006)
Dewan dictionary Arab Malay